2022
DOI: 10.1111/cas.15295
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐penetrating peptide internalizing RGD enhances radiotherapy efficacy through reducing tumor hypoxia

Abstract: Resistance to irradiation (IR) remains a major therapeutic challenge in tumor radiotherapy. The development of novel tumor-specific radiosensitizers is crucial for effective radiotherapy against solid tumors. Here, we revealed that remodeling tumor tissue penetration via tumor-penetrating peptide internalizing arginine-glycine-aspartic acid RGD (iRGD) enhanced irradiation efficacy. The growth of 4T1 and CT26 multicellular tumor spheroids (MCTS) and tumors was delayed significantly by the treatment with IR and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The following biological processes can affect radiation resistance in both the tumor and the microenvironment around it: changed DNA damage response (DDR) and increased DNA repair; hypoxia; cancer stem cell repopulation; altered cell cycle; inflammation; altered management of oxidative stress; altered mitochondrial function and cellular energetics (3,(16)(17)(18)(19)(20)(21). We previously described the remodeling tumor tissue penetration via tumor-penetrating peptide iRGD enhanced radiation efficacy and summarized the molecular mechanism for this type of peptide: peptide iRGD can reduced hypoxia and enhanced the efficacy of radiation through MRP-1 (7). Notably, LyP-1 also can reduce hypoxia (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following biological processes can affect radiation resistance in both the tumor and the microenvironment around it: changed DNA damage response (DDR) and increased DNA repair; hypoxia; cancer stem cell repopulation; altered cell cycle; inflammation; altered management of oxidative stress; altered mitochondrial function and cellular energetics (3,(16)(17)(18)(19)(20)(21). We previously described the remodeling tumor tissue penetration via tumor-penetrating peptide iRGD enhanced radiation efficacy and summarized the molecular mechanism for this type of peptide: peptide iRGD can reduced hypoxia and enhanced the efficacy of radiation through MRP-1 (7). Notably, LyP-1 also can reduce hypoxia (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In previous work, we described a remodeling tumor tissue penetration via tumor-penetrating peptide internalizing arginine-glycine-aspartic acid RGD (iRGD) enhanced radiation efficacy, and applied the peptide to treat mice with 4T1 tumor ( 7 ). The iRGD contain three independent modules: vascular homing sequence, R/KXXR/K tissue penetration sequence, and protease recognition site ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…iRGD was initially used for tumor-specific delivery of small-molecule compounds ( 11 ). Previously, we found in vivo and in vitro experiments that free iRGD can increase the radiosensitivity of breast cancer cells 4T1 via remodeling tumor tissue penetration ( 17 ). However, free iRGD is quickly metabolized by the body’s liver and spleen.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study reported for the first time that the modification of iRGD could improve the cancer-specific lymphocyte infiltration in both mouse models and 3D cancer spheroids ( 16 ). Recently, we demonstrated that iRGD could enhance irradiation efficacy via remodeling tumor tissue penetration ( 17 ). However, the feasibility of employment of iRGD for RBC modification has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia plays a key role in mediating irradiation resistance and iRGD allows the diffusion of oxygen molecules into tumor tissues alleviating hypoxia. 77 The ProteoChip system was used to develop twelve α v β 3 -antagonistic peptides from the hexapeptide library. Interestingly, the two hexapeptides with the highest antiangiogenic and antimetastatic activities contained the Ser–Asp–Val (SDV) and Gly–Asp–Val (GDV) sequences.…”
Section: Types Of Acps and Their Mode Of Actionmentioning
confidence: 99%